2018
DOI: 10.5562/cca3289
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulosic Materials as Dye Adsorbents: Adsorption of Methylene Blue and Congo Red on Brewers’ Spent Grain

Abstract: Brewers' spent grain (BSG), a lignocellulosic waste material, was evaluated as a low-cost adsorbent for the removal of synthetic dyes methylene blue (MB) and Congo red (CR) from aqueous solutions in a batch process. Characterisation of the BSG was performed by chemical analysis, FTIR and SEM. The effects of contact time, initial dye concentration, adsorbent particle size, adsorbent concentration and pH on the adsorption process were investigated. High removal of both dyes ranging from 70 to over 90 % was achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 46 publications
2
16
0
1
Order By: Relevance
“…From the plot, it could be observed that the amount of MEB adsorbed increased as the concentration increased. This observation is in line with the studies [38,26] on the removal of MEB through brewers spent mint adsorptive capacity and retama raetam. Sorption capacity increased as the initial MEB concentration increased from 0.095 mg/g to 0.2 mg/g and equilibrium was attained indicating increased fractional MEB adsorption.…”
Section: Effect Of Initial Meb Concentration and Time Of Contactsupporting
confidence: 92%
See 1 more Smart Citation
“…From the plot, it could be observed that the amount of MEB adsorbed increased as the concentration increased. This observation is in line with the studies [38,26] on the removal of MEB through brewers spent mint adsorptive capacity and retama raetam. Sorption capacity increased as the initial MEB concentration increased from 0.095 mg/g to 0.2 mg/g and equilibrium was attained indicating increased fractional MEB adsorption.…”
Section: Effect Of Initial Meb Concentration and Time Of Contactsupporting
confidence: 92%
“…Surface area and pore size of the ARHB determined from BET surface area plot are 9.369 cc/g and 27.32 m 2 /g respectively and represented in Figure 2. The XRD patterns of ARHB ( Figure 3) contained only a broad peak that is characteristic of amorphous phase silica common among biochars carbonized below 600 o C (38). BET surface area analysis and XRD analysis of ARHB showed amorphous nature and nanosize forms of the biochar respectively [2,12,49] .…”
Section: Nature Of Sorbentmentioning
confidence: 99%
“…The effect of contact time on the removal of methylene blue dye when using fir wood sawdust as adsorbent material is given in Fig. 3 which shows the potential of the adsorbent material in the process of retaining the methylene blue dye due to the presence of lignocellulosic components (cellulose, hemicellulose and lignin) in the sawdust structure that are mainly responsible for the adsorption process [23]. The adsorption is achieved through the interaction of dyes and functional groupsmainly hydroxyl and carboxyl groupsof these polymers [23].…”
Section: Influence Of Contact Timementioning
confidence: 99%
“…Proses adsorpsi terjadi akibat interaksi antara zat warna dan gugus fungsi dari polimer-polimer tersebut (seperti -OH dan -COOH) (Kezerle, 2018).…”
Section: Pendahuluanunclassified